Kesiapan Guru Sekolah Dasar Dalam Mengimplementasikan Projek P5 Dimensi Wirausaha Pada Kurikulum Merdeka Kelas IV Sekolah Dasar - Arista Alchosiyah; Flesia Welly Ferianti (JURNAL PENDIDIKAN DAN PEMBELAJARAN SEKOLAH DASAR, 2026)
Abstract: The research aims to analyze the readiness of fourth-grade teachers at SDN 09 Tanjung Lay in implementing the entrepreneurship dimension of the Pancasila Student Profile Strengthening Project (P5) within the Independent Curriculum. The research method used is descriptive qualitative. The research subject is the fourth-grade teacher at SDN 09 Tanjung Lay. Research instruments include interview sheets, observation sheets, and documentation guidelines. Data collection techniques employed interviews, observation, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing, with data validity checked using triangulation techniques. The results showed that the readiness of fourth grade teachers in SDN 09 Tanjung Lay in implementing the entrepreneurship dimension in P5 illustrates a structured and oriented readiness for continuous improvement, with teachers increasing conceptual understanding and having independent curriculum principles. Teachers are able to make relevant project-based learning planning, choose appropriate materials, methods, and media, and have pedagogical skills in applying interactive and contextual methods that involve active students. Teachers also demonstrate a professional attitude with commitment and enthusiasm in innovative project activities, attend training and receive school support, and conduct evaluations and reflections to improve learning effectiveness. Factors affecting teacher readiness is the availability of learning resources that are still limited. This study shows that the readiness of teachers in carrying out the project P5 entrepreneurship dimension is influenced by training, school support, and the availability of learning resources. Keywords: Teacher Readiness, Implementation of Entrepreneurship Dimension, Pancasila Student Profile Strengthening Project (P5), Independent Curriculum. Abstrak: Penelitian bertujuan menganalisis kesiapan guru kelas IV SDN 09 Tanjung Lay dalam mengimplementasikan dimensi kewirausahaan pada Projek Penguatan Profil Pelajar Pancasila (P5) dalam Kurikulum Merdeka. Metode penelitian menggunakan kualitatif deskriptif. Subjek penelitian guru kelas IV SDN 09 Tanjung Lay. Instrumen penelitian meliputi lembar wawancara, lembar observasi, dan pedoman dokumentasi. Teknik pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Analisis data dilakukan melalui reduksi data, penyajian data, dan penarikan kesimpulan, serta pengecekan keabsahan data menggunakan triangulasi teknik. Hasil penelitian menunjukkan bahwa kesiapan guru kelas IV di SDN 09 Tanjung Lay dalam mengimplementasikan dimensi kewirausahaan pada P5 menggambarkan kesiapan yang terstruktur dan berorientasi pada peningkatan berkelanjutan, dengan guru meningkatkan pemahaman konseptual dan memiliki prinsip Kurikulum Merdeka. Guru mampu membuat perencanaan pembelajaran berbasis projek yang relevan, memilih materi, metode, dan media yang sesuai, serta memiliki keterampilan pedagogis dalam menerapkan metode interaktif dan kontekstual yang melibatkan siswa aktif. Guru juga menunjukkan sikap profesional dengan komitmen dan antusiasme dalam kegiatan projek yang inovatif, mengikuti pelatihan dan mendapat dukungan sekolah, serta melakukan evaluasi dan refleksi untuk meningkatkan efektivitas pembelajaran. Faktor memengaruhi kesiapan guru adalah ketersediaan sumber belajar yang masih terbatas. Penelitian ini menunjukkan bahwa kesiapan guru dalam menjalankan projek P5 dimensi kewirausahaan dipengaruhi oleh pelatihan, dukungan sekolah, dan ketersediaan sumber belajar. Kata Kunci: Kesiapan Guru, Implementasi Dimensi Kewirausahaan, Projek Penguatan Profil Pelajar Pancasila (P5), Kurikulum Merdeka